Safety Tourism Policy in Bali: Infrastructure Challenges and Sustainable Public Management - Dewi, Nyoman Diah Utari; Mahendra, Putu Denny Artina; Hanafiah, Mohd Hafiz (Jurnal Manajemen Pelayanan Publik, 2025)
Bali is globally renowned as a popular tourist destination, celebrated for its natural beauty and cultural diversity, which serve as the main economic driver for the region. Despite the existence of regulations and policies concerning tourism safety, considerable challenges remain in their practical implementation. The primary issues stem from inadequate infrastructure development and limited government facilitation, resulting in suboptimal safety facilities and systems at various tourism sites. These conditions pose a risk of accidents and threaten tourist safety, ultimately diminishing confidence in Bali’s tourism sector. This study employs a qualitative, descriptive approach, combining direct observation and literature review to assess the safety and infrastructure conditions across multiple tourist destinations. It utilizes the tourism aspect framework to analyze the current situation related to safety and infrastructure. Furthermore, to provide effective recommendations for policymakers, this research adopts the sense of safety towards a tourist destination concept from Zou & Yu, aiming to comprehensively measure and understand tourists perceptions of safety. The findings indicate that many destinations in Bali have yet to implement effective and policy-compliant safety systems. The sense of safety towards a tourist destination approach highlights the critical roles of social actors, infrastructure, as well as human and technological factors in creating a secure and comfortable environment. An integrated approach is anticipated to enhance safety standards and restore tourist confidence in Bali’s destinations.